Open Learning, Distance Education and Transformative Learning: An Agenda for Action and its Challenges - Adu, I.F; Salawu, I.O; Ojo, Olugbenga D.; Inegbedion, Juliet; Ogidan, Rotimi (West African Journal of Open and Flexible Learning, 2014)
Nations all over the world are fast accepting the open and distance learning mode as the option that creates access and opportunity for education for all irrespective of location, position and age. It is an avenue for capacity building and human capital development in terms of the quality output required in the world of work and nation's economy. There has been a persistent call for a review of the pedagogical strategies in use in our schools. Transformative learning that involves a structural shift is being considered as an alternative to -the traditional teaching-learning pedagogy. Therefore, this paper explored the concept of open learning, distance education and the integration of characteristics of transformative learning as they relate to teaching and learning activities for the purpose of pedagogical outcomes in terms of learning goals and objectives. The question is, can open and distance learning serve as a good medium for transformative learning. Some of the benefits of transformative learning particularly in the area of giving recognition to certificates that are earned from open and distance learning institutions are mentioned while the challenges of transformative learning as it affects teaching and learning are discussed.
Keywords: Open Learning; Distance Education